2016
DOI: 10.1128/cvi.00243-16
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Serogroup C: Current Status of Vaccines and Why They Are Needed

Abstract: Nontyphoidal Salmonella (NTS; i.e., Salmonella enterica organisms that do not cause typhoid or paratyphoid) are responsible for 94 million infections and 155,000 deaths worldwide annually, 86% of which are estimated to be foodborne. Although more than 50 serogroups and 2,600 serovars have been described, not all Salmonella serovars cause disease in humans and animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 67 publications
3
55
0
Order By: Relevance
“…Salmonella Kentucky ST198 is an emerging public health threat and is more commonly associated with clinical disease in humans in Europe and in people with a travel history to Africa and the Middle East. Salmonella Kentucky ST152, the serotype found in this study, is commonly isolated from healthy, asymptomatic poultry and cattle (CDC, ; CDC, ; Fuche, Sow, Simon, & Tennant, ; Vosik, Tewari, Dettinger, M'ikanatha, & Shariat ). While human cases of salmonellosis have been attributed to poultry‐associated ST152, its pathogenicity to humans is questionable, it has caused fewer cases of salmonellosis in humans compared to serovars Typhimurium, Enteritidis, Newport and Heidelberg among others, and to date, it has not been associated with a large‐scale food‐borne outbreak of salmonellosis (Foley et al, ; Howe et al, ; Shah, Paul, Sischo, Crespo, & Guard, ).…”
Section: Discussionmentioning
confidence: 87%
“…Salmonella Kentucky ST198 is an emerging public health threat and is more commonly associated with clinical disease in humans in Europe and in people with a travel history to Africa and the Middle East. Salmonella Kentucky ST152, the serotype found in this study, is commonly isolated from healthy, asymptomatic poultry and cattle (CDC, ; CDC, ; Fuche, Sow, Simon, & Tennant, ; Vosik, Tewari, Dettinger, M'ikanatha, & Shariat ). While human cases of salmonellosis have been attributed to poultry‐associated ST152, its pathogenicity to humans is questionable, it has caused fewer cases of salmonellosis in humans compared to serovars Typhimurium, Enteritidis, Newport and Heidelberg among others, and to date, it has not been associated with a large‐scale food‐borne outbreak of salmonellosis (Foley et al, ; Howe et al, ; Shah, Paul, Sischo, Crespo, & Guard, ).…”
Section: Discussionmentioning
confidence: 87%
“…Infantis as predominantly present in the poultry industry worldwide (Fuche et al . ) and cause substantial economic losses (Rajagopal and Mini ). In the United States, S .…”
Section: Introductionmentioning
confidence: 99%
“…More than 2700 serotypes of Salmonella have been reported (Wu et al 2016). Studies have shown S. Infantis as predominantly present in the poultry industry worldwide (Fuche et al 2016) and cause substantial economic losses (Rajagopal and Mini 2013). In the United States, S.…”
Section: Introductionmentioning
confidence: 99%
“…The areas where NTS disease is prevalent are located mostly in sub-Saharan Africa, as well as in south Asian countries, because of poor health care systems, malnutrition, and possible zoonotic transmission (7)(8)(9). Through food contamination, episodic outbreaks are also reported in developed countries, which may be caused by other serogroups, including O:7 and O:8 (10)(11)(12)(13). In 2010, the estimated burden of NTS infection accounted for 93.8 million cases and 155,000 casualties (14).…”
Section: Introductionmentioning
confidence: 99%